How does a lifestyle intervention during pregnancy influence perceived barriers to leisure-time physical activity? The Norwegian fit for delivery study, a randomized controlled trial - Lene A. H. Haakstad (BMC Pregnancy and Childbirth, 2018)
Abstract Background To develop effective health promotional and preventive prenatal programs, it is important to understand perceived barriers to leisure-time physical activity during pregnancy, including exercise and sport participation. The aims of the present study was 1) to assess the effect of prenatal lifestyle intervention on the perceived barrier to leisure-time physical activity during pregnancy and the first year after delivery and 2) identify the most important perceived barriers to leisure-time physical activity at multiple time points during and after pregnancy. Methods This secondary analysis was part of the Norwegian Fit for Delivery study, a combined lifestyle intervention evaluated in a blinded, randomized controlled trial. Healthy, nulliparous women with singleton pregnancy of ≤20 gestational weeks, age ≥ 18 years and body mass index ≥19 kg/m2 were recruited via healthcare clinics in southern Norway, including urban and rural settings. Participants were randomized to either twice-weekly supervised exercise sessions and nutritional counselling (n = 303) or standard prenatal care (n = 303). The principal analysis was based on the participants who completed the standardized questionnaire assessing their perceived barriers to leisure-time physical activity at inclusion (gestational week 16, n = 589) and following intervention (gestational week 36, n = 509), as well as six months (n = 470) and 12 months (n = 424) postpartum. Results Following intervention (gestation week 35.4 ± 1.0), a significant between-group difference in perceived barriers to leisure-time physical activity was found with respect to time constraints: “... I do not have the time” (intervention: 22 vs. control: 38, p = 0.030), mother-child safety concerns: “... afraid to harm the baby” (intervention: 8 vs. control: 25, p = 0.002) and self-efficacy: “... I do not believe/think that I can do it” (intervention: 3 vs. control: 10, p = 0.050). No positive effect was seen at postpartum follow-up. Intrapersonal factors (lack of time, energy and interest) were the most frequently perceived barriers, and consistent over time among all participants. Conclusion The intervention had effect on intrapersonal perceived barriers in pregnancy, but not in the postpartum period. Perceived barriers to leisure-time physical activity were similar from early pregnancy to 12 months postpartum. Trial registration ClinicalTrials.gov: NCT01001689, registered July 2, 2009.